Agricultural Credit and Profitability of MV Boro Rice Cultivation at Farm Level in Some Selected Areas of Chapai Nawabganj District (Journal of the Bangladesh Agricultural University, 2020)
Agricultural credit program is considered as the significant change-maker in the rural and subsistence agriculture sector of Bangladesh. Attainment of the agricultural credit program typically relies on the disbursement process, effective utilization as well as the profitability of the ultimate users. Therefore, an investigation was conducted at Sadar and Nachol Upazila under Chapai Nawabganj district to assess the amount of requirement and disbursement situation of credit; evaluate the cost of getting credit and its utilization patterns; measure the profitability of credit borrowers; and find out the constraints of getting credit by different farm categories to get a detailed insight about successful attainment of the credit program on modern variety (MV) Boro rice cultivation. A total of 120 borrower farmers belonging equally to small, medium and large categories of farm who took a loan from Rajshahi Krishi Unnayan Bank (RAKUB) were interviewed in 2018. Descriptive statistics as well as tabular analysis were used to analyze and interpret the data. The findings revealed that on an average RAKUB fulfilled 77% of the total credit requirement of Boro rice farmers in the study areas. Borrowers had to pay on an average Tk 12.18 for getting hundred taka loans where small farmers had to pay the highest followed by medium and large farmers, respectively. Small, medium and large farmers used 48, 35 and 23 percent of borrowed money, respectively, for Boro rice production and the rest were used for family consumption and other purposes. Medium farmers were found to be more profitable followed by large and small borrower farmers, respectively. Insufficient amount of credit, higher non-interest cost of institutional credit as well as long and complex institutional procedure of loan disbursement was reported as main constraints by the borrowers. Findings highlight the inevitability of reformation of the current agricultural credit program to make it more user-friendly and an effective contrivance.J Bangladesh Agril Univ 18(3): 667–673, 2020https://doi.org/10.5455/JBAU.99065